2000
DOI: 10.1063/1.870249
|View full text |Cite
|
Sign up to set email alerts
|

Periodic arrays of gyrotactic plumes in bioconvection

Abstract: Using the continuum model of Pedley et al. ͓J. fluid Mech. 195, 223 ͑1988͔͒ for bioconvection in a suspension of swimming, gyrotactic microorganisms , the existence and stability of periodic arrays of two-dimensional plumes in deep chambers are investigated. The system is governed by the Navier-Stokes equations for an incompressible fluid coupled with a microorganism conservation equation. These equations are solved numerically using a conservative finite-difference scheme. In sufficiently deep chambers, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Since these microorganisms are typically 3-5% heavier than water, the density of the suspension in the regions of downflow becomes larger than in the regions of upflow. Buoyancy increases velocity fluctuations in both upflow and downflow regions thus introducing a hydrodynamic instability [2][3][4]. The induced convection fluid motion causes the development of bioconvection plumes.…”
Section: P Geng and A V Kuznetsovmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these microorganisms are typically 3-5% heavier than water, the density of the suspension in the regions of downflow becomes larger than in the regions of upflow. Buoyancy increases velocity fluctuations in both upflow and downflow regions thus introducing a hydrodynamic instability [2][3][4]. The induced convection fluid motion causes the development of bioconvection plumes.…”
Section: P Geng and A V Kuznetsovmentioning
confidence: 99%
“…Governing equations for a bioconvection plume caused by gyrotactic microorganisms are given in References [3,4] as:…”
Section: Dimensional Governing Equationsmentioning
confidence: 99%
“…Ghorai and Hill [2,3] have shown that if the inertia terms in the momentum equation are neglected (which is justiÿed for bioconvection ows because of a very low Reynolds number), the vectorp, which determines the swimming direction of microorganisms, can be computed asp…”
Section: Dimensionless Governing Equationsmentioning
confidence: 99%
“…Governing equations for a bioconvection plume caused by gyrotactic microorganisms are given in References [2,3] as Continuity equation…”
Section: Dimensional Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation